2011
DOI: 10.1371/journal.pone.0017054
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan Crosslinking Relaxation Plays an Important Role in Staphylococcus aureus WalKR-Dependent Cell Viability

Abstract: The WalKR two-component system is essential for viability of Staphylococcus aureus, a major pathogen. We have shown that WalKR acts as the master controller of peptidoglycan metabolism, yet none of the identified regulon genes explain its requirement for cell viability. Transmission electron micrographs revealed cell wall thickening and aberrant division septa in the absence of WalKR, suggesting its requirement may be linked to its role in coordinating cell wall metabolism and cell division. We therefore teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
75
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 68 publications
7
75
0
Order By: Relevance
“…From the microarray data, we could neither estimate the biological function of walK* nor confirm the activation or deactivation of WalRK due to introduction of walK*, since there was only one gene (SA0710) downregulated by walK* introduction out of nine genes that have been reported to be directly regulated by the walRK system (21,22). Recently, Delaune et al reported on the effect of walRK on cell morphology, showing that walRK depletion could raise the cell wall thickness of S. aureus (19). As the mutant into which walK* was introduced, LR5P1walK*, had a thickened cell wall, it might be reasonable to consider that walK* might hamper the function of the walRK system, but its regulatory pathway toward cell wall thickening remains to be studied.…”
Section: Fig 4 Growth Curves (A) and Autolytic Activities (B) Of Gementioning
confidence: 96%
“…From the microarray data, we could neither estimate the biological function of walK* nor confirm the activation or deactivation of WalRK due to introduction of walK*, since there was only one gene (SA0710) downregulated by walK* introduction out of nine genes that have been reported to be directly regulated by the walRK system (21,22). Recently, Delaune et al reported on the effect of walRK on cell morphology, showing that walRK depletion could raise the cell wall thickness of S. aureus (19). As the mutant into which walK* was introduced, LR5P1walK*, had a thickened cell wall, it might be reasonable to consider that walK* might hamper the function of the walRK system, but its regulatory pathway toward cell wall thickening remains to be studied.…”
Section: Fig 4 Growth Curves (A) and Autolytic Activities (B) Of Gementioning
confidence: 96%
“…An alternative mechanism assumes that monolaurin is able to interfere with bacterial two-component regulatory systems. Monolaurin was found to inhibit WalK/R, one of the 16 two-component regulatory systems in S. aureus, leading to the death of the bacteria (33). In this study, we observed direct confirmation of the disruption of bacterial cell walls; however, the second mechanism could also play a role, as it was not studied here.…”
Section: Discussionmentioning
confidence: 54%
“…2A, lanes 3-4), in agreement with previously published data. 30 A much longer transcript with a size corresponding to SA0264-lytM was detected at all growth phases with slight variation in the 2 genetic (HG001 and RN4220) backgrounds ( Fig. 2A, lanes 1-12).…”
mentioning
confidence: 93%
“…29 Interestingly, SsaA and LytM are the only 2 proteins that can by-pass WalKR essentiality by modifying the peptidoglycan cross-peptide bridges. 30 Other findings have indicated that the translation of lytM mRNA is regulated through RNAIII binding. 31 Therefore, in addition to the regulation of several virulence factors, 29 RNAIII coordinates the repression of several cell wall hydrolases at the late-exponential phase of growth.…”
Section: Introductionmentioning
confidence: 99%